1990
DOI: 10.1007/bf02277294
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of naphthoquinones from Fusaria

Abstract: Twenty-two naphthoquinone compounds isolated or derived synthetically from culture extracts of Fusarium solani and F. oxysporum were examined for antimicrobial activity. Fifteen exhibited antibiotic activity against Staphylococcus aureus, and 12 were active against Streptococcus pyogenes, but none were active at the highest rate of 128 micrograms/ml against Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Proteus vulgaris, Serratia marcescens, or Pseudomonas aeruginosa. Of 8 plant pathogenic bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…These were allowed to stay for three hours before incubating at 30°C for 24 h (Boonphong et al, 2001). The plates were examined after 48 h and the diameter zone of inhibition (DZ1) for each test organisms was recorded (Baker et al, 1990). (Table 3).…”
Section: Determination Of Antimicrobial Activity Of Actinomycetes Isomentioning
confidence: 99%
“…These were allowed to stay for three hours before incubating at 30°C for 24 h (Boonphong et al, 2001). The plates were examined after 48 h and the diameter zone of inhibition (DZ1) for each test organisms was recorded (Baker et al, 1990). (Table 3).…”
Section: Determination Of Antimicrobial Activity Of Actinomycetes Isomentioning
confidence: 99%
“…nHexane soluble fraction was obtained only in three strains which showed mild toxicity. Antimicrobial naphthoquinones are widely distributed in plants, fungi and some animals (Riffel et al, 2002) are also reported from F. solani (Ammar et al, 1979;Baker et al, 1990). Besides naphthoquinones, F. solani is also known to produce diterpene and paclitaxel (Chakravarthi et al, 2008), and has been used alone or in combination with other chemotherapeutic agents for the treatment of variety of cancers, as well as AIDS-related Kaposi sarcoma (Brown, 2003;Croom, 1995 Means of 3 replicates.…”
Section: Resultsmentioning
confidence: 99%
“…F. solani is known to produce naphthoquinone compounds (Baker et al, 1990) including fusarubin, anhydrofusarubin, javanicin, norjavanicin, methyl etherfusarubin, marticin, isomarticin, bostrycoidia, ethyl ether-fusarubin, solaniol, nectriafusarubin and dihydrofusarubin lactone (James & Robert 1983;Kurobane et al, 1980;Tatum et al, 1985). Some naphthaquinones have antimicrobial, toxic, insecticidal and antitumor properties (Ammar et al, 1979).…”
mentioning
confidence: 99%
“…Secondary metabolites like fusarubin and its derivatives isolated from Fusarium sp. are also known for their antibacterial activity (Baker et al, 1990). The present study revealed that secondary metabolites isolated from F. oxysporum f. sp.…”
Section: Anti-nemic Activitymentioning
confidence: 93%